KESEIMBANGAN HIDUP DALAM AL-QUR’AN: TELAAH TAFSIR TARBAWY - Nur Lailatul Lusiana; Zakiya Faridatul Fatimah, Saila Muna, Ana Rahmawati (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
Islam teaches a balance between the life of this world and the hereafter as two complementary aspects. A Muslim is obliged to work hard in this world with the intention of accumulating provisions for the afterlife. The world is not considered the ultimate goal, but rather a means to eternal happiness in the hereafter. In the Islamic view, the worldly life is a test and an opportunity to worship, do good, and get closer to Allah. Islam emphasises that balance must be struck in all aspects of life, including between spirit and matter, mind and heart, and rights and duties. This principle is also emphasised in the Quran, particularly in QS. Al-Qashash verse 77, which reminds people not to forget their part of the world, but also to use it for the good of the hereafter. Islam does not advocate abandoning the world completely, but rather utilising it wisely as a means to gain happiness in the hereafter. In addition, Islamic teachings emphasise the importance of doing good and avoiding damage on earth, in accordance with Allah's commands in various verses of the Quran. Thus, the balance of the world and the hereafter is the key to living a life in harmony with the purpose of human creation